Analisis Tindak Tutur Representatif dalam Daftar Putar “TPS – Literasi dalam Bahasa Indonesia pada Kanal Youtube Privat Alfaiz” - Seruni Yunita Chairunnisa; Nadia Nurul Arofah; Nukti Wahyu Ilhami; Alifia Khoirun Nisa; Primastuti Nugraheni; Widi Rahayu; Asep Purwo Yudi Utomo; Faizal Arvianto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
his study aims to identify the representative speech acts contained in the learning video on the playlist “TPS-Literasi dalam Bahasa Indonesia” from the Private Al Faiz channel. In this study, the author aims to examine the purpose of the speech conveyed by Febri Irawan Al Faiz in the Private Al Faiz youtube channel. In speech acts, there are representative speech acts. Representative speech acts are speech acts that bind the speaker to the truth of what is said. The approaches used in this research are theoretical approach and methodological approach. This research uses the listening method with the note method as a continuation and also uses the commensurate method. The results of this study found that speech acts containing representative as follows: (1) explain, (2) demand, (3) state, (4) acknowledge, (5) show, (6) conclude, (7) suggest, (8) assert. From the six videos that have been analyzed, 324 speech acts are produced, namely 95 speech acts of explaining, 26 speech acts of demanding, 26 speech acts of stating, 18 speech acts of admitting, 61 speech acts of showing, 22 speech acts of concluding, 40 speech acts of suggesting, and 36 speech acts of affirming.